Primary proximal urethral adenocarcinoma: Case report and brief review - Siosaki, Marcos Duarte; Machado, Roberto Dias; Souza, Ana Tarsila Fonseca; Magnabosco, Wesley Justino; Santos, Alexandre Cesar; Gonçalves, Fernando Zapparoli; Pereira, Fernando Coutinho; Silva, Carlos Flávio de Araújo; Faria, Eliney Ferreira (Canadian Urological Association Journal, 2013)
Primary urethral cancer in females is rare. It has a poor prognosis. The published data on this topic are limited, composed mostly of small case series. This paper presents a case of an advanced adenocarcinoma of the urethra, intestinal type, treated with anterior exenteration.